'Help UMP students master STEM' - UMP, PNC (The New Straits Times Press (M) Bhd., 2018)
KUANTAN: Regent of Pahang Tengku Abdullah Sultan Ahmad Shah has urged Universiti Malaysia Pahang (UMP) to take the lead in developing rural students interest in Science, Technology, Engineering and Mathematics (STEM).